2009
DOI: 10.1501/egifak_0000001179
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Variables Which Explain the Behavior of Academic Procrastination in University Students

Abstract: ABSTRACT. The purpose of the study was to investigate if academic motivation, anxiety, time management, general procrastination and irrational beliefs predicted academic procrastination behaviour. Participants (N=250) were the students attending different faculties of Ankara University. The Academic Procrastination Scale (Yorulmaz, Çakıcı ve Gülebağlan, 2003), the Irrational Beliefs Scale (Türküm, 1999), the Learning and Study Strategies Inventory (Köymen, 1994) and the General Procrastination Scale (Yorulmaz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
2
9
0
4
Order By: Relevance
“…Results of this study with aim to examine the prevalence of academic negligence among students, implying that more than half of the students in relation to academic tasks in frequently, often, or always, are negligence. These results are largely consistent with the findings of many researchers (eg, Solomon & Ruthbloom, 1984;Kagan, 2009;Ferrari, Johnson, & McDonald, 2005;Klasn et al, 2008;Hariot & Ferrari, 1996) based on negligence is the high rate of school.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results of this study with aim to examine the prevalence of academic negligence among students, implying that more than half of the students in relation to academic tasks in frequently, often, or always, are negligence. These results are largely consistent with the findings of many researchers (eg, Solomon & Ruthbloom, 1984;Kagan, 2009;Ferrari, Johnson, & McDonald, 2005;Klasn et al, 2008;Hariot & Ferrari, 1996) based on negligence is the high rate of school.…”
Section: Discussionsupporting
confidence: 89%
“…10;2015 On gender, the academic negligence researches, has largely equivocal, different, ambiguous and complex. Some of these studies (e.g., Ferrari et al, 1995;Kagan, 2009;Ozer & Dmyrvfrary, 2009) suggest that males are more lax .However, other studies indicate that there is not significant relationship between gender and negligence (Clark & Hill, 1994;Haykvk, 1993;Solomon & Ruthblum, 1984). The results also indicate that there wasn't a significant relationship between gender and educational neglect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balkıs et al (2006) showed that the academic procrastination tendency had a significant positive correlation with the negative attitudes toward learning, learning difficulties and concentration difficulties. The work of Kağan (2009) on university students show that there is a positive and significant correlation between academic procrastination and general procrastination whereas there is a weak significant and negative correlation between academic procrastination and anxiety. Onwuegbuzie (2004) also reported that individuals who experience increases in levels of statistics anxiety are more likely to postpone undertaking statistical activities and assignments (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The relevant literature gives several definitions of the term. Kağan (2009) defines the academic procrastination behavior as the problems with which students face when they try to prepare their studies related to exams and projects on time. In another definition which focuses on the underlying reasons of academic procrastination behavior, Senecal, Julien and Gay (2003) mention the tendency to delay starting and carrying on academic assignments because of illogical reasons.…”
Section: Introductionmentioning
confidence: 99%